Effect of microalgal carotenoid extract on the viability of two melanoma cell lines: the role of oxidative stress - Schetinger, Luisa Chitolina (2023)
Microalgae have been attracting great attention due to their richness of bioactive compounds and nutrients. They are excellent sources of protein, lipids, carbohydrates, natural pigments, and numerous carotenoids. However, the interest in their potential goes beyond the food industry. They can be applied in the production of biodiesel, wastewater treatment, and even in the development of novel medicines. They are the fundamental basis of aquatic ecosystems. One of the most intriguing characteristics of these organisms is their intense coloration, which comes from various pigments. These pigments are essential for the survival of microalgae and are molecules that actively participate in their photosynthetic metabolism. Pigments also have an important biological action, promoting health and being the focus of new discoveries that help to renew modern medicine. Thus, in this study, an in vitro model was used to investigate the effect of carotenoid extract from Scenedesmus obliquus against melanoma cells. The viability of A375 and B16F10 melanoma cells was measured after treatment with the carotenoid extract, and the carotenoids absorbed by the cells were identified using HPLC-PDA-MS/MS. In addition, the impact of the treatment on the concentrations of reactive oxygen species (ROS) and nitric oxide (NO) in the melanoma cells was evaluated. The results demonstrated that treatment with the carotenoid extract caused a significant (p < 0.05) decrease in A375 and B16F10 cells viability in a dose-dependent manner, with IC50 values of 40.30 μg/ml and 13.24 μg/ml for A375 and B16F10 cells, respectively. During the treatment, the melanoma cells absorbed six carotenoids, including all-trans-lutein, all-trans-zeaxanthin, 2’-dehydrodeoxymyxol, 5,6-epoxide-β-carotene, all-trans-echinenone, and all-trans-α-carotene. Of these carotenoids, four were detected in both types of cells (all-trans-lutein, all-trans-zeaxanthin, 5,6-epoxide-β-carotene, and all-trans-α-carotene), while the B16F10 cells absorbed two additional compounds (2’-dehydrodeoxymyxol and all-trans-echinenone). Moreover, the treatment with the carotenoid extract significantly increased the concentrations of ROS, NO, and caspase-1 in both A375 and B16F10 cells. Therefore, the carotenoid extract from Scenedesmus obliquus acted as a cytotoxic and pro-apoptotic agent, reducing the viability of A375 and B16F10 melanoma cells. These findings suggest that carotenoids may have potential as collaborators in cancer management.